Core-shell Fe3O4/SiO2/TiO2 Magnetic Modified Ag for the Photocatalytic Degradation of Congo Red Dye and Antibacterial Activity - Poedji Loekitowati Hariani; Salni Salni; Muhammad Said; Rahfi Farahdiba (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Disposal of dye wastewater can induce detrimental consequences for human health and the environment. The study aims to synthesize composites consisting of core-shell Fe3O4/SiO2/TiO2 modified with Ag. The composites comprise a Fe3O4 core, a SiO2 interlayer, and a TiO2 shell, with Ag being mobilized on the surface of the core and shell structures. Fe3O4/SiO2/TiO2@Ag composite was employed in the photocatalytic degradation of Congo red dye and antibacterial activity test. The degradation was facilitated by visible light irradiation while considering different factors such as pH solution, the photocatalyst dosage, and the dye's initial concentration. The composite was characterized using X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Scanning Electron Microscopy-Electron Dispersive X-ray Spectroscopy (SEM-EDS), Vibrating Sample Magnetometer (VSM), and UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS). The findings indicated that the composite exhibited strong magnetic, measuring 49.4 emu/g, with a band gap of 2.92 eV. The composite showed commendable catalytic properties, with degradation efficiency of 96.52% for Congo red dye under conditions: a pH solution of 4, a dosage of 0.5 g/L, and a dye concentration of 10 mg/L at 100 min of irradiation. The photocatalytic degradation kinetic is align with pseudo-first-order reactions. The composite also exhibits remarkable stability and efficiency with 4.83% decline in degradation efficiency after five cycles. Fe3O4/SiO2/TiO2@Ag composite exhibited antibacterial activity against Escherichia coli and Staphylococcus aureus with a Minimum Inhibitory Concentration (MIC) value of 250 mg/L. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).